Inhibition of Zinc Dendrites in Zinc-Based Flow Batteries - Guo, Leibin; Guo, Hui; Huang, Haili; Tao, Shuo; Cheng, Yuanhui (Frontiers in Chemistry, 2020)
Zinc-based flow batteries have gained widespread attention and are considered to be one of the most promising large-scale energy storage devices for increasing the utilization of intermittently sustainable energy. However, the formation of zinc dendrites at anodes has seriously depressed their cycling life, security, coulombic efficiency, and charging capacity. Inhibition of zinc dendrites is thus the bottleneck to further improving the performance of zinc-based flow batteries, but it remains a major challenge. Considering recent developments, this mini review analyzes the formation mechanism and growth process of zinc dendrites and presents and summarizes the strategies for preventing zinc dendrites by regulating the interfaces between anodes and electrolytes. Four typical strategies, namely electrolyte modification, anode engineering, electric field regulation, and ion transfer control, are comprehensively highlighted. Finally, remaining challenges and promising directions are outlined and anticipated for zinc dendrites in zinc-based flow batteries.